(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
Personal Knowledge Management (PKM) is very crucial for students to manage their own knowledge and activities in learning. However, previous PKM system development in academia lacks user involvement during development, resulting in the final system design not aligning with students’ actual workflow and causing low usability. In this study, the prototype of the web-based PKM system will be designed with iterative user-centered design (UCD) that centers on the students for the design of the system solutions. The research adopts four phases of UCD: user and context identification, specification of user requirements, design of the solutions, and usability evaluation. User personas were created through literature review and contextual observations. The prototype was designed with Figma and tested with the System Usability Scale (SUS), initially involving 16 students from UMM in their fifth semester and above, with 15 valid responses analyzed after excluding one extreme outlier. A SUS score of 71.17 ± 14.59, with a 95% confidence interval of [63.09–79.25], places the system in the "Acceptable" (Grade C) category. This shows that the UCD approach can successfully develop a moderately usable PKM system, which still needs further improvement in learnability to better address students’ problems in the document management process.